Respostas
respondido por:
2
a) ![81^{0,12}\cdot 81^{0,13}=3 81^{0,12}\cdot 81^{0,13}=3](https://tex.z-dn.net/?f=81%5E%7B0%2C12%7D%5Ccdot+81%5E%7B0%2C13%7D%3D3)
![81^{0,12+0,13}=3\\ \\ 81^{0,25}=3\\ \\ \left(3^{4} \right )^{0,25}=3\\ \\ 3^{4\,\cdot\,0,25}=3\\ \\ 3^{1}=3 81^{0,12+0,13}=3\\ \\ 81^{0,25}=3\\ \\ \left(3^{4} \right )^{0,25}=3\\ \\ 3^{4\,\cdot\,0,25}=3\\ \\ 3^{1}=3](https://tex.z-dn.net/?f=81%5E%7B0%2C12%2B0%2C13%7D%3D3%5C%5C+%5C%5C+81%5E%7B0%2C25%7D%3D3%5C%5C+%5C%5C+%5Cleft%283%5E%7B4%7D+%5Cright+%29%5E%7B0%2C25%7D%3D3%5C%5C+%5C%5C+3%5E%7B4%5C%2C%5Ccdot%5C%2C0%2C25%7D%3D3%5C%5C+%5C%5C+3%5E%7B1%7D%3D3)
A sentença acima é verdadeira.
b)
(
)
![a^{\,^{1}\!\!\!\diagup\!\!_{2}-\,^{1}\!\!\!\diagup\!\!_{4}}=a^{\,^{1}\!\!\!\diagup\!\!_{4}}\\ \\ a^{\,^{1}\!\!\!\diagup\!\!_{4}}=a^{\,^{1}\!\!\!\diagup\!\!_{4}} a^{\,^{1}\!\!\!\diagup\!\!_{2}-\,^{1}\!\!\!\diagup\!\!_{4}}=a^{\,^{1}\!\!\!\diagup\!\!_{4}}\\ \\ a^{\,^{1}\!\!\!\diagup\!\!_{4}}=a^{\,^{1}\!\!\!\diagup\!\!_{4}}](https://tex.z-dn.net/?f=a%5E%7B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7B2%7D-%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7B4%7D%7D%3Da%5E%7B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7B4%7D%7D%5C%5C+%5C%5C+a%5E%7B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7B4%7D%7D%3Da%5E%7B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7B4%7D%7D)
É válido para qualquer valor de
.
c)![\sqrt[n]{a}\cdot \sqrt[m]{a}=\sqrt[nm]{a^{2}} \sqrt[n]{a}\cdot \sqrt[m]{a}=\sqrt[nm]{a^{2}}](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7Ba%7D%5Ccdot+%5Csqrt%5Bm%5D%7Ba%7D%3D%5Csqrt%5Bnm%5D%7Ba%5E%7B2%7D%7D)
![a^{\,^{1}\!\!\!\diagup\!\!_{n}}\cdot a^{\,^{1}\!\!\!\diagup\!\!_{m}}=a^{\,^{2}\!\!\!\diagup\!\!_{nm}}\\ \\ a^{\,^{1}\!\!\!\diagup\!\!_{n}+\,^{1}\!\!\!\diagup\!\!_{m}}=a^{\,^{2}\!\!\!\diagup\!\!_{nm}}\\ \\ \dfrac{1}{n}+\dfrac{1}{m}=\dfrac{2}{mn}\\ \\ \dfrac{m+n}{mn}=\dfrac{2}{mn}\\ \\ m+n=2 a^{\,^{1}\!\!\!\diagup\!\!_{n}}\cdot a^{\,^{1}\!\!\!\diagup\!\!_{m}}=a^{\,^{2}\!\!\!\diagup\!\!_{nm}}\\ \\ a^{\,^{1}\!\!\!\diagup\!\!_{n}+\,^{1}\!\!\!\diagup\!\!_{m}}=a^{\,^{2}\!\!\!\diagup\!\!_{nm}}\\ \\ \dfrac{1}{n}+\dfrac{1}{m}=\dfrac{2}{mn}\\ \\ \dfrac{m+n}{mn}=\dfrac{2}{mn}\\ \\ m+n=2](https://tex.z-dn.net/?f=a%5E%7B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7Bn%7D%7D%5Ccdot+a%5E%7B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7Bm%7D%7D%3Da%5E%7B%5C%2C%5E%7B2%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7Bnm%7D%7D%5C%5C+%5C%5C+a%5E%7B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7Bn%7D%2B%5C%2C%5E%7B1%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7Bm%7D%7D%3Da%5E%7B%5C%2C%5E%7B2%7D%5C%21%5C%21%5C%21%5Cdiagup%5C%21%5C%21_%7Bnm%7D%7D%5C%5C+%5C%5C+%5Cdfrac%7B1%7D%7Bn%7D%2B%5Cdfrac%7B1%7D%7Bm%7D%3D%5Cdfrac%7B2%7D%7Bmn%7D%5C%5C+%5C%5C+%5Cdfrac%7Bm%2Bn%7D%7Bmn%7D%3D%5Cdfrac%7B2%7D%7Bmn%7D%5C%5C+%5C%5C+m%2Bn%3D2)
Esta sentença não é válida para todos os valores de
,
e
.
A sentença acima é verdadeira.
b)
É válido para qualquer valor de
c)
Esta sentença não é válida para todos os valores de
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás